2012
DOI: 10.1177/1358863x12459650
|View full text |Cite
|
Sign up to set email alerts
|

Low yield of genetic testing for known vascular connective tissue disorders in patients with fibromuscular dysplasia

Abstract: Patients with fibromuscular dysplasia (FMD) may have clinical features consistent with Mendelian vascular connective tissue disorders. The yield of genetic testing for these disorders among patients with FMD has not been determined. A total of 216 consecutive patients with FMD were identified. Clinical characteristics were collected and genetic test results reviewed for abnormalities in the following genes: transforming growth factor-β receptor 1 and 2 (TGFβR1 and TGFβR2), collagen 3A1, fibrillin-1, smooth mus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 47 publications
4
39
0
Order By: Relevance
“…Poloskey and colleagues 49 demonstrated that the prevalence of genetic mutations associated with connective tissue disorders, including the COL31A gene, transforming growth factor (TGF)-β1 and β2 genes, and the ACTA2 gene, was negligible in an FMD cohort. In their case series, however, they report 2 patients with distinct novel point mutations in the TGF-β receptor type 1 gene, mutations of which have been associated with inherited aneurysmal disease.…”
Section: Genetic Considerationsmentioning
confidence: 99%
See 3 more Smart Citations
“…Poloskey and colleagues 49 demonstrated that the prevalence of genetic mutations associated with connective tissue disorders, including the COL31A gene, transforming growth factor (TGF)-β1 and β2 genes, and the ACTA2 gene, was negligible in an FMD cohort. In their case series, however, they report 2 patients with distinct novel point mutations in the TGF-β receptor type 1 gene, mutations of which have been associated with inherited aneurysmal disease.…”
Section: Genetic Considerationsmentioning
confidence: 99%
“…In their case series, however, they report 2 patients with distinct novel point mutations in the TGF-β receptor type 1 gene, mutations of which have been associated with inherited aneurysmal disease. 49,50 Both patients with these TGF-β receptor type 1 mutations had multifocal disease (medial fibroplasia), had suffered carotid or vertebral artery dissection, had ascending aortic dilatation, and had a family history of sudden death. 49 In summary, evidence supports a genetic basis for susceptibility to FMD.…”
Section: Genetic Considerationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Accordingly, it may be postulated that there is a continuum between both forms and that, alongside with environmental factors, genetic factors may also contribute to the pathogenesis of apparently sporadic FMD. Earlier case-control studies failed to show an association between FMD and variants of genes coding for components of the renin-angiotensin system 51 and extracellular matrix, 52 including α-1 antitrypsin. 53 However, a large association study looking for enrichment in gene variants in patients with sporadic FMD compared with controls disclosed a significant association between multifocal FMD and 3 genes coding for muscle proteins (OBSCN, DYNC2H1, and MYLK), one of them (MYLK) also involved in familial thoracic aortic dissection, and a fourth one associated with susceptibility to Moyamoya disease (RNF213).…”
Section: Genetics Of Fmdmentioning
confidence: 99%